"Nothing goes as planned": Practitioners reflect on matching children and foster families. Issue 3 (27th February 2018) - Zeijlmans, Kirti; López, Mónica; Grietens, Hans; Knorth, Erik J.
Abstract: Matching children with foster carers is an important step in every nonkinship family foster care placement. Although guidelines for matching are provided in several studies, the case‐specific context of the decision can influence the practitioners' ability to adhere to these guidelines. Therefore, this study answers the following question: "How does the case‐specific context influence the practitioners' decision‐making process regarding matching in family foster care?" Using a qualitative design, 20 semistructured interviews were conducted with practitioners matching children with foster families. Three themes emerged representing different layers of practitioners' everyday decision‐making: matching as planned, matching being tailored, and matching being compromised. The results show that exceptions are part of practitioners' daily work, either due to the belief that it might benefit those involved or because of obstacles presented during the decision‐making process. When the decision is compromised, matching practitioners lower their standards, while at the same time safeguarding the quality of the match. This proves that matching in practice is more than choosing a family, and guidelines are needed to determine what "good‐enough" matching should entail.